Fundamentals of information studies : - Lester, June (Neal-Schuman Publishers, 2007)
The book has fourteen chapters covered The Impact of Information in Society and Fundamental Concepts of Information ; look at The Information Professions and The Impact of Information Cultures and Societies ; and conclude with Information Ethics and Information Futures. Appropriate emphasis is placed throughout on the history and development of information technology. Every chapter has been thoroughly updated and revised